An investigation of factors influencing communities decision to reside in gated development in Kuala Lumpur and Selangor - Mohamed Osman, Mariana; Rabe, Noor Suzilawati; Bachok, Syahriah (2011)
This research investigates the underlying factors influencing the development of gated and guarded communities in Malaysia. The main objectives of the research is to ascertain whether the increasing demand over the neighbourhood concept was merely due to the needs to exert better control and security over their living environment or due to other factors such as privacy and affluent lifestyle. Therefore, questionnaire survey and interviews were conducted among the stakeholders, namely the residents, local planning authorities and developers to examine this issue from different perspectives. The research further discussed on the implications of gated and guarded neighbourhood, which investigated whether or not, gated communities reflected social and economic segregation among the residents and its surroundings.The research concluded that gated development can create social separation between communities. In addition, accessibility was limitation to the public, thus was not appropriate and in tandem with inclusive residential planning and layout design that promoted mixed use development, diversity and street connectivity.